2018
DOI: 10.3389/fphar.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Compound From Paeoniflorin, CP-25, Suppressed Immune Responses and Synovium Inflammation in Collagen-Induced Arthritis Mice

Abstract: Paeoniflorin-6’-O-benzene sulfonate (CP-25) is a modified paeoniflorin, which is the main bioactive component of total glucosides of peony. This study evaluated the anti-inflammatory and immunoregulatory effects of CP-25 in mice with collagen-induced arthritis (CIA) and the potential mechanisms underlying these effects. After the onset of CIA, mice were given CP-25 (17.5, 35, or 70 mg/kg) or methotrexate (MTX, 2.0 mg/kg). The arthritis index, swollen joint count, and joint and spleen histopathology were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…IgD-Fc-Ig had no significant effect on anti-CD3/CD28 antibody-stimulated cells. Activated T cells, together with high expression of CD69 and CD154 (CD40L), play vital roles in RA-associated inflammation by producing inflammatory cytokines, which induce synovium inflammation and immune responses (33,34). We previously demonstrated that IgD increases the percentage of CD69 + and CD154 + cells, which might contribute to the elevated IgDR expression and Lck tyrosine phosphorylation (19).…”
Section: Discussionmentioning
confidence: 99%
“…IgD-Fc-Ig had no significant effect on anti-CD3/CD28 antibody-stimulated cells. Activated T cells, together with high expression of CD69 and CD154 (CD40L), play vital roles in RA-associated inflammation by producing inflammatory cytokines, which induce synovium inflammation and immune responses (33,34). We previously demonstrated that IgD increases the percentage of CD69 + and CD154 + cells, which might contribute to the elevated IgDR expression and Lck tyrosine phosphorylation (19).…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of the reagent was 2 mg/mL. After overnight storage at 4 • C, 0.1 mL reagent was injected into the bottom of the tail of DBA/1 mice, and the same dose was injected into the back again after 21 days [17]. Mice were divided into normal group and CIA model group (n = 8 per group).…”
Section: The Establishment Of Cia Modelmentioning
confidence: 99%
“…3A,B).We found that most of genes were related to the response to immune, Cancer immunotherapy is a breakthrough in cancer, such as cytokine therapy [34]. previous articles have con rmed the in ammation and immunity of paeoni orin in diseases such as rheumatoid [38], allergic asthma [39] and arthritis [40]. In addition, the GO analysis results also explain that paeoni orin is also involved in cell migration [17,41], cell activation, and cell activity regulation.…”
Section: Discussionmentioning
confidence: 55%